Syrian Arab Republic : 2006 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
The economic recovery since 2004 has been accompanied by a steady rise in inflation. Several factors have contributed, including an expansionary monetary stance (with credit to the private sector growing by some 45 percent). Although pleased with the recent improvement of the economy, the authorities are increasingly concerned with the considerable risks involved in delaying adjustment and in postponing structural reforms. The authorities were encouraged to see that the implementation of their broad-based reforms elicited a positive supply response.